WORK-RETIREMENT TRANSITIONS AND SOCIAL RELATIONS - Wan, W. (Innov Aging, 2017)
The Convoy Model of Social Relations posits that changes in social networks have important implications for social support, health, and well-being. The Social Relations Study (Waves 1 to 3) provides a unique opportunity to examine changes in social networks over 20 years. This study tests the Strength and Vulnerability Integration (SAVI) model and the Socioemotional Selectivity Theory (SST) as competing theories to examine changes between work status (working versus retired) and network characteristics. Bivariate analyses revealed that those who remained working (n=251) from Wave 1 to Wave 3 had more promixate networks (73.5%), more negative networks (M=2.2; t=3.1, p<.01), and less positive networks (M=4.7; t=-3.5, p<.001) than those who retired (n=154; 66% promixate networks; M=1.9 negative networks; M=4.8 positive networks). Findings are discussed using the Convoy Model to elaborate ways in which the SAVI and SST frameworks advance a lifespan perspective on roles and social relations.